Method for producing circuit connection adhesive and connection structure

The conductive particle adhesive with a specific metal-to-ceramic core ratio maintains excellent electrical conductivity in flexible displays by addressing the issue of oxide film formation on titanium electrodes, ensuring reliable connections in COP implementations.

JP7622448B2Active Publication Date: 2025-01-28RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021007930
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-21
Publication Date
2025-01-28
Estimated Expiration
2041-01-21

AI Technical Summary

Technical Problem

The formation of an oxide film on the surface of circuit electrodes, particularly those made of titanium, leads to increased connection resistance, which is a challenge in flexible displays using plastic substrates (COP) where electrical conductivity between electrodes is compromised.

Method used

A conductive particle adhesive is developed with a metal layer covering the base particles and a ceramic core material that raises the outer surface of the metal layer, maintaining a D1/L1 ratio of 0.75 to 1.25, ensuring excellent electrical conductivity even with an oxide film formation.

Benefits of technology

The adhesive provides a connection structure with superior electrical conductivity between electrodes, effectively mitigating the impact of oxide films on circuit performance in flexible displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622448000008
    Figure 0007622448000008
  • Figure 0007622448000009
    Figure 0007622448000009
  • Figure 0007622448000010
    Figure 0007622448000010
Patent Text Reader

Abstract

To provide a circuit connection adhesive agent capable of obtaining a connection structure with an excellent electrical conductivity between opposed electrodes even in a case where an oxide film is formed on an electrode surface of a circuit member.SOLUTION: Provided is a circuit connection adhesive agent 1 containing conductive particles 4. Each conductive particle 4 has a base material particle, a metal layer coating of the base material particle surface, and a ceramic core arranged in the metal layer to make an outer surface of the metal layer protrude. When a thickness of the metal layer is defined as d1 and a length of the ceramic core in a thickness direction of the metal layer is defined as l1, d1 / l1 is 0.75 to 1.25.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an adhesive for circuit connection and a method for producing a connection structure. [Background technology]

[0002] In display devices such as liquid crystal display devices and organic EL panels, in order to achieve fine pitch, light weight and thinness, so-called COG (chip on glass) technology is adopted, in which semiconductor elements such as driver ICs are mounted directly on the glass substrate of the display panel.

[0003] In a liquid crystal display panel that employs the COG mounting method, for example, a semiconductor element such as a liquid crystal driving IC is connected to a transparent substrate (such as a glass substrate) that has a plurality of transparent electrodes (such as ITO (indium tin oxide)). The driving IC has a plurality of electrode terminals formed on its mounting surface that correspond to the transparent electrodes, and is thermocompression bonded to the transparent substrate via a circuit connecting adhesive (such as an anisotropic conductive adhesive film), thereby connecting the electrode terminals to the transparent electrodes via conductive particles contained in the circuit connecting adhesive.

[0004] In recent years, displays with curved surfaces (flexible displays) have been proposed. In such flexible displays, flexible plastic substrates (polyimide substrates, etc.) are used as the base material instead of glass substrates, and so-called COP (chip on plastic) in which semiconductor elements such as driving ICs are directly mounted on the plastic substrate has been studied (see Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Laid-Open No. 2016-54288 Summary of the Invention [Problem to be solved by the invention]

[0006] Incidentally, an oxide film may form on the surface of the electrodes of a circuit component, and when an oxide film forms on the surface of an electrode, the electrical conductivity between the opposing electrodes deteriorates. In particular, since titanium is mainly used as the material for the electrodes (circuit electrodes) of the circuit board in COPs, an oxide film (titanium oxide film) is likely to form on the surface of the circuit electrodes, which tends to increase the connection resistance between the opposing electrodes.

[0007] Therefore, the main object of the present invention is to provide an adhesive for circuit connection that can obtain a connection structure having excellent electrical conductivity between opposing electrodes, even if an oxide film is formed on the surface of the electrodes of a circuit component. [Means for solving the problem]

[0008] The present inventors have investigated ways to improve electrical conductivity by forming protrusions on the surface of conductive particles that can penetrate an oxide film. As a result, they have found that, in coated conductive particles having a metal layer on the surface of a base particle, conductive particles having protrusions on the surface can be obtained by disposing a core material within the metal layer to raise the surface of the metal layer, and that excellent electrical conductivity can be obtained even when an oxide film is formed on the surface of an electrode by selecting the thickness of the metal layer, the size of the core material, and the material constituting the core material in the conductive particles.

[0009] That is, one aspect of the present invention relates to an adhesive for circuit connection shown in [1] below.

[0010] [1] A circuit connection adhesive containing conductive particles, the conductive particles having a base particle, a metal layer covering the surface of the base particle, and a ceramic core material disposed within the metal layer and raising the outer surface of the metal layer, wherein the thickness of the metal layer is d1 and the length of the ceramic core material in the thickness direction of the metal layer is l1, and the circuit connection adhesive has a ratio d1 / l1 of 0.75 to 1.25.

[0011] According to the circuit connection adhesive of the above aspect, even if an oxide film is formed on the surface of the electrodes of the circuit component, a connection structure having excellent electrical conductivity between opposing electrodes can be obtained.

[0012] The circuit connecting adhesive on the side may be any of the circuit connecting adhesives shown in [2] to

[11] below.

[0013] [2] The adhesive for circuit connection according to [1], wherein the thickness d1 of the metal layer is 110 to 190 nm.

[0014] [3] The adhesive for circuit connection according to either [1] or [2], which contains a thermosetting compound, a latent curing agent, and a thermoplastic resin.

[0015] [4] The adhesive for circuit connection according to [3], wherein the thermosetting compound is at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds.

[0016] [5] The circuit connecting adhesive according to [3] or [4], wherein the thermoplastic resin is a phenoxy resin.

[0017] [6] The adhesive for circuit connection according to any one of [1] to [5], which is in the form of a film.

[0018] [7] The circuit connection adhesive described in [6], comprising a first adhesive layer containing the conductive particles and a second adhesive layer provided on the first adhesive layer.

[0019] [8] The adhesive for circuit connection according to [7], wherein the first adhesive layer contains a cured product of a photocurable component.

[0020] [9] The adhesive for circuit connection according to [8], wherein the first adhesive layer further contains a thermosetting component.

[0021]

[10] The adhesive for circuit connection according to any one of [1] to [9], which is used to connect a plastic substrate with circuit electrodes to a semiconductor element.

[0022]

[11] The circuit connection adhesive according to

[10] , wherein the circuit electrode contains titanium on the connection surface.

[0023] Another aspect of the present invention relates to a method for producing a connection structure as shown in

[12] below.

[0024]

[12] A method for manufacturing a connection structure, comprising the steps of: placing a circuit connection adhesive according to any one of [1] to

[11] between a first circuit member having a first electrode and a second circuit member having a second electrode; and thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other via the conductive particles. [Effects of the Invention]

[0025] According to the present invention, an adhesive for circuit connection is provided that can obtain a connection structure having excellent electrical conductivity between opposing electrodes, even when an oxide film is formed on the surface of the electrode of a circuit component. [Brief explanation of the drawings]

[0026] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of a film-like adhesive for circuit connection. [Figure 2] 2 is a schematic cross-sectional view showing conductive particles used in the circuit connection adhesive of FIG. 1. FIG. [Figure 3] FIG. 3 is a partially enlarged view of a cross section of the conductive particle shown in FIG. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a connection structure according to an embodiment. [Figure 5] FIG. 5 is a schematic cross-sectional view showing a manufacturing process of a connection structure according to one embodiment. DETAILED DESCRIPTION OF THE INVENTION

[0027] In this specification, "(meth)acrylate" means at least one of acrylate and its corresponding methacrylate. The same applies to other similar expressions such as "(meth)acrylic" and "(meth)acryloyl." Furthermore, "A or B" may include either A or B, or may include both. Furthermore, "room temperature" means 25°C.

[0028] Unless otherwise specified, the materials exemplified below may be used alone or in combination of two or more. When multiple substances corresponding to each component are present in the composition, the content of each component in the composition refers to the total amount of the multiple substances present in the composition, unless otherwise specified. Furthermore, numerical ranges indicated using "to" indicate ranges that include the numerical values ​​before and after "to" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range may be replaced with the upper or lower limit of a numerical range in another stage. Furthermore, in the numerical ranges described in this specification, the upper or lower limit of that numerical range may be replaced with the value shown in the examples. Furthermore, the upper and lower limits individually described can be combined in any combination.

[0029] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments in any way.

[0030] <Circuit connection adhesive> The circuit connection adhesive comprises a base particle, a metal layer covering the surface of the base particle, and a ceramic core material disposed within the metal layer and elevating the outer surface of the metal layer, and contains conductive particles in which d1 / l1 is 0.75 to 1.25, where d1 is the thickness of the metal layer and l1 is the length of the ceramic core material in the thickness direction of the metal layer.

[0031] The circuit connection adhesive may further contain, as components other than the conductive particles, for example, a thermosetting compound and a latent curing agent, which are thermosetting components, and a thermoplastic resin. The circuit connection adhesive may be interposed between a first circuit member having a first electrode and a second circuit member having a second electrode, and used to electrically connect the first and second electrodes to each other by thermocompression bonding the first and second circuit members.

[0032] The circuit connection adhesive described above can provide a connection structure (circuit connection structure) that exhibits excellent electrical conductivity between opposing electrodes, even when an oxide film is formed on the surface of the electrodes of a circuit component. Therefore, the circuit connection adhesive described above is suitable for use in COP mounting using titanium-containing electrodes, which are prone to forming an oxide film on the surface of the electrodes of a circuit component. More specifically, the adhesive can be used to connect a plastic substrate with circuit electrodes to a semiconductor element such as a driving IC.

[0033] While the reason for the above-mentioned effect is unclear, the inventors speculate as follows. First, in the conductive particles, the protruding portions of the outer surface of the metal layer due to the core material come into contact with the surface of the electrode before the non-protruding portions (flat portions). However, since the core material is made of a hard ceramic, the conductive particles can easily penetrate the oxide film. On the other hand, because a ceramic core material is used, if the core material is too large compared to the thickness of the metal layer, the metal layer on the core material may break, resulting in an increase in connection resistance. However, by keeping the ratio (d1 / l1) within the above range, it is possible to raise the outer surface of the metal layer while suppressing breakage of the metal layer. It is speculated that the above-mentioned effect is achieved for the above-mentioned reasons.

[0034] The circuit connecting adhesive is, for example, in the form of a film. Hereinafter, the circuit connecting adhesive will be described in detail using a film-like circuit connecting adhesive (circuit connecting adhesive film) having a two-layer structure as an example.

[0035] Figure 1 is a diagram schematically showing a longitudinal cross section of an adhesive film for circuit connection according to one embodiment. The adhesive film for circuit connection 1 (hereinafter also simply referred to as "adhesive film 1") shown in Figure 1 is an anisotropically conductive adhesive film that includes a first adhesive layer 2 and a second adhesive layer 3 provided on the first adhesive layer 2. Note that the "longitudinal cross section" refers to a cross section (cross section in the lamination direction) that is perpendicular to the main surface (for example, the main surface of the adhesive film 1).

[0036] (First adhesive layer) The first adhesive layer 2 contains conductive particles 4 and an adhesive component 5 that disperses the conductive particles 4. In this specification, all components contained in the first adhesive layer 2 other than the conductive particles 4 are collectively referred to as the adhesive component 5.

[0037] [Conductive particles] Fig. 2 is a cross-sectional view schematically illustrating one embodiment of a conductive particle 4, and Fig. 3 is a partially enlarged view of the cross section of the conductive particle 4 shown in Fig. 2. As shown in Fig. 2 and Fig. 3, the conductive particle 4 has a base particle 41, a metal layer 42 that covers a surface 41a of the base particle 41, and a ceramic core material 43 that is disposed within the metal layer 42 and raises the outer surface 42a of the metal layer 42. On the surface of the conductive particle 4, protrusions 44 are formed by the raised outer surface 42a of the metal layer 42.

[0038] Examples of the base particle 41 include resin particles, inorganic particles other than metal particles, organic-inorganic hybrid particles, metal particles, etc. The base particle 41 may be a core-shell particle having a core (e.g., an organic core) and a shell (e.g., an inorganic shell) disposed on the surface of the core.

[0039] Examples of resins for forming resin particles and organic-inorganic hybrid particles include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polyalkylene terephthalate, polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyethersulfone, and polymers obtained by polymerizing one or more of various polymerizable monomers having an ethylenically unsaturated group.

[0040] Examples of inorganic substances for forming inorganic particles and organic-inorganic hybrid particles include silica, alumina, barium titanate, zirconia, and carbon black.

[0041] The particle diameter of the base particle 41 may be, for example, 2 to 5 μm. When the base particle 41 has a shape other than a perfect sphere, the maximum diameter of the base particle is taken as the particle diameter.

[0042] Although there may be a portion of the surface 41a of the base particle 41 that is not covered with the metal layer , it is preferable that the entire surface 41a of the base particle 41 is covered with the metal layer .

[0043] The metal layer 42 is composed of one or more metals. Examples of metals that may be used in the metal layer 42 include gold, silver, copper, palladium, ruthenium, rhodium, iridium, lithium, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. When the metal layer 42 contains at least one metal selected from the group consisting of nickel and palladium, the connection resistance between opposing electrodes tends to be further reduced. The nickel content may be 50% by mass or more, 75% by mass or more, or 90% by mass or more, and 100% by mass or less, based on the total mass of the metal layer 42. The palladium content may be 50% by mass or more, 75% by mass or more, or 90% by mass or more, and 100% by mass or less, based on the total mass of the metal layer 42.

[0044] Metal layer 42 may have a multilayer structure (a structure of two or more layers). For example, from the viewpoint of further reducing the connection resistance between opposing electrodes, metal layer 42 may have a nickel layer (a layer containing 90% or more by mass of nickel) and a palladium layer (a layer containing 90% or more by mass of palladium).

[0045] The metal layer 42 may be, for example, an electrolytic plated layer formed by electrolytic plating, or an electroless plated layer formed by electroless plating. The metal layer may have both an electrolytic plated layer and an electroless plated layer.

[0046] The metal layer 42 has a flat portion 42b where the ceramic core material 43 is not present between the outer surface 42a and the surface 41a of the base particle, and the outer surface 42a is flat, and a raised portion 42c where the outer surface 42a is raised by the ceramic core material 43. The raised portion 42c constitutes a protrusion 44 formed on the surface of the conductive particle 4.

[0047] The thickness d1 of the metal layer 42 may be 110 nm or more, 130 nm or more, or 150 nm or more from the viewpoint of making the metal layer less likely to break during connection. The thickness d1 of the metal layer 42 may be 190 nm or less, 160 nm or less, or 140 nm or less from the viewpoint of further reducing the connection resistance between the opposing electrodes.

[0048] The thickness d1 of the metal layer 42 is the thickness of the flat portion 42b of the metal layer 42. The thickness d1 of the metal layer 42 is determined by cutting the conductive particle 4 along a plane passing through the center C (the center of the base particle 41) and measuring the shortest distance from the surface of the flat portion 42b of the metal layer 42 to the surface 41a of the base particle in the cut cross section.

[0049] The thickness d2 of the raised portion 42c of the metal layer 42 may be 150 nm or more, 180 nm or more, or 250 nm or more from the viewpoint of conductivity between opposing circuits. The thickness d2 of the raised portion 42c of the metal layer 42 may be 500 nm or less, 400 nm or less, or 300 nm or less from the viewpoint of insulation between adjacent circuits. The thickness d2 is the thickness of the thickest point of the raised portion 42c, and can be determined in the same manner as the measurement of the thickness d1, by measuring the shortest distance from the tip 44a of the protrusion 44 to the surface 41a of the base particle.

[0050] A plurality of ceramic core materials 43 are arranged in the metal layer 42 , and a plurality of protrusions 44 are formed on the surface of the conductive particle 4 by raising the outer surface 42 a of the metal layer 42 .

[0051] The ceramic core 43 has a length l1 in the thickness direction of the metal layer 42. In this embodiment, the ratio (d1 / l1) of the thickness d1 of the metal layer 42 to the length l1 is 0.75 to 1.25. When the ratio (d1 / l1) is in the above range, a connection structure with excellent electrical conductivity between opposing electrodes is obtained.

[0052] The ratio (d1 / l1) may be 0.90 or more or 1.00 or more from the viewpoint of making it less likely for the metal layer to break during connection, and may be 1.10 or less or 0.95 or less from the viewpoint of further reducing the connection resistance between opposing electrodes.

[0053] The thickness-wise length l1 of the metal layer 42 of the ceramic core material 43 may be 100 nm or more, 150 nm or more, or 250 nm or more in order to further reduce the connection resistance between opposing electrodes, and may be 400 nm or less, 300 nm or less, or 200 nm or less in order to make it less likely that the metal layer will break during connection.

[0054] The length l1 of the ceramic core 43 in the thickness direction of the metal layer 42 is determined by cutting the conductive particle 4 along a plane passing through the center C (the center of the base particle 41) and the tip 44a of the protrusion 44, measuring the longest distance from the center C to the ceramic core 43 and the shortest distance from the center C to the ceramic core 43 on the cut cross section, and calculating the difference between these measured values.

[0055] The length l2 of the ceramic core material 43 in the extending direction of the metal layer 42 is not particularly limited, but may be, for example, 100 to 300 nm. The length l2 can be measured in the same manner as the length l1.

[0056] The ceramic core material 43 may be attached to the surface 41a of the substrate particle 41, or may be located away from the surface 41a of the substrate particle 41. The shortest distance d3 from the surface of the ceramic core material 43 to the surface 41a of the substrate particle 41 may be, for example, 0 to 50 nm. The shortest distance d4 from the surface of the ceramic core material 43 to the outer surface 42a of the metal layer 42 may be, for example, 50 to 100 nm. The shortest distances d3 and d4 can be measured in the same manner as the length l1.

[0057] The ceramic core 43 is made of one or more ceramic materials, such as titanium oxide, alumina, silicon nitride, and zirconia.

[0058] The shape of the ceramic core material 43 is not particularly limited, but may be, for example, particulate. That is, the ceramic core material may be ceramic particles. The particle shape may be, for example, spherical, blocky, needle-like, columnar, flake-like, or approximately spherical.

[0059] The number of ceramic cores 43 (the number of protrusions 44) in the conductive particle 4 may be, for example, 5 to 30.

[0060] The average particle size of the conductive particles 4 may be, for example, 1 to 18 μm from the viewpoint of excellent dispersibility and conductivity. In this embodiment, the particle sizes of 300 random conductive particles (pcs) are measured by observation using a scanning electron microscope (SEM), and the average value of the obtained particle sizes is defined as the average particle size of the conductive particles 4. Note that, since the conductive particles 4 in this embodiment have protrusions 44, the particle size of the conductive particles is defined as the diameter of a circle circumscribing the conductive particle in the SEM image.

[0061] The conductive particles 4 can be obtained, for example, by a method in which a ceramic core material 43 is attached to the surface 41a of a substrate particle 41, and then a metal layer 42 is formed on the substrate particle 41 and the ceramic core material 43. Alternatively, the conductive particles 4 may be obtained by a method in which a first metal layer is formed on the surface 41a of the substrate particle 41, then a ceramic core material 43 is attached to the surface of the first metal layer, and then a second metal layer is formed on the first metal layer and the ceramic core material 43. The first metal layer and the second metal layer may be the same or different.

[0062] Methods for adhering the ceramic core material 43 to the substrate particles 41 include adding the ceramic core material 43 to a dispersion of the substrate particles 41 and, for example, using van der Waals forces to cause the ceramic core material to accumulate and adhere to the surface 41a of the substrate particles 41, and adding the ceramic core material 43 to a container containing the substrate particles 41 and causing the ceramic core material 43 to adhere to the surface 41a of the substrate particles 41 through mechanical action such as rotating the container.

[0063] The metal layer 42 may be formed by, for example, plating (electrolytic plating or electroless plating).

[0064] The content of the conductive particles 4 may be 10 to 60 mass %, or may be 20 to 60 mass %, based on the total mass of the circuit connecting adhesive. When the content of the conductive particles is 10 mass % or more, good conductivity is easily obtained, and when the content of the conductive particles is 60 mass % or less, short circuits in the connection structure are easily suppressed.

[0065] The content of the conductive particles 4 may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the total mass of the first adhesive layer, from the viewpoint of further improving conductivity. The content of the conductive particles 4 may be 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the first adhesive layer, from the viewpoint of easily suppressing short circuits. The content of the conductive particles 4 (based on the total mass of the composition) in a composition (first adhesive composition) for forming the first adhesive layer, which will be described later, may be the same as the above range.

[0066] [Adhesive ingredients] The adhesive component 5 contains, for example, a cured product of a photocurable component (hereinafter sometimes referred to as "component (A)") and / or a thermosetting component (hereinafter sometimes referred to as "component (B)"). The cured product of the photocurable component may be a cured product obtained by completely curing the photocurable component, or a cured product obtained by partially curing the photocurable component. When the adhesive component 5 contains a cured product of the photocurable component and a thermosetting component, electrical conductivity between opposing electrodes tends to be further improved.

[0067] (A): Photocurable component There are no particular limitations on component (A), so long as it is a component (e.g., a resin component) that cures upon exposure to light. Component (A) includes, for example, a photocurable compound (hereinafter sometimes referred to as "component (A1)") and a curing agent for the photocurable compound (hereinafter sometimes referred to as "component (A2)"). Note that if the cured product of component (A) is thermosetting, the cured product (thermosetting cured product) does not fall under the category of component (B).

[0068] -(A1): Photocurable compound The component (A1) may be, for example, a radically polymerizable compound (hereinafter, sometimes referred to as "component (A1-1)") or a cationically polymerizable compound (hereinafter, sometimes referred to as "component (A1-2)").

[0069] --(A1-1): Radical polymerizable compound The component (A1-1) has at least one radically polymerizable group. Examples of the radically polymerizable group include (meth)acryloyl, vinyl, allyl, styryl, alkenyl, alkenylene, and maleimide groups. The number of radically polymerizable groups (functional groups) in the component (A1-1) may be 2 or more, from the viewpoints of easily achieving a desired melt viscosity after polymerization, further improving the effect of reducing connection resistance, and providing superior connection reliability, and may be 10 or less, from the viewpoint of suppressing cure shrinkage during polymerization. Furthermore, in order to balance crosslink density and cure shrinkage, in addition to compounds having the number of radically polymerizable groups within the above range, compounds having the number of radically polymerizable groups outside the above range may be used.

[0070] To suppress the flow of conductive particles, the component (A1-1) may contain a (meth)acrylate compound as a radical polymerizable compound. The (meth)acrylate compound may be a monofunctional (meth)acrylate having one (meth)acryloyl group, or a polyfunctional (meth)acrylate having two or more (meth)acryloyl groups, or these may be used in combination.

[0071] Examples of monofunctional (meth)acrylates include (meth)acrylic acid; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, butoxyethyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, octylheptyl (meth)acrylate, and nonyl (meth)acrylate. Decyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolypropylene glycol (meth)acrylate, mono(2-(meth)acryloyloxy) Aliphatic (meth)acrylates such as diethyl succinate; benzyl (meth)acrylate, phenyl (meth)acrylate, o-biphenyl (meth)acrylate, 1-naphthyl (meth)acrylate, 2-naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, p-cumylphenoxyethyl (meth)acrylate, o-phenylphenoxyethyl (meth)acrylate, 1-naphthoxyethyl (meth)acrylate, 2-naphthoxyethyl (meth)acrylate, phenoxypolyether aromatic (meth)acrylates such as ethylene glycol (meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, phenoxy polypropylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-hydroxy-3-(o-phenylphenoxy)propyl (meth)acrylate, 2-hydroxy-3-(1-naphthoxy)propyl (meth)acrylate, and 2-hydroxy-3-(2-naphthoxy)propyl (meth)acrylate;Examples of such acrylates include (meth)acrylates having an epoxy group such as glycidyl (meth)acrylate, (meth)acrylates having an alicyclic epoxy group such as 3,4-epoxycyclohexylmethyl (meth)acrylate, and (meth)acrylates having an oxetanyl group such as (3-ethyloxetan-3-yl)methyl (meth)acrylate.

[0072] Examples of polyfunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetrapropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, and 1,3-butane. aliphatic (meth)acrylates such as diol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 2-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, glycerin di(meth)acrylate, tricyclodecane dimethanol (meth)acrylate, and ethoxylated 2-methyl-1,3-propanediol di(meth)acrylate;Aromatic (meth)acrylates such as ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, ethoxylated propoxylated bisphenol A di(meth)acrylate, ethoxylated bisphenol F di(meth)acrylate, propoxylated bisphenol F di(meth)acrylate, ethoxylated propoxylated bisphenol F di(meth)acrylate, ethoxylated fluorene di(meth)acrylate, propoxylated fluorene di(meth)acrylate, and ethoxylated propoxylated fluorene di(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, ethoxylated propoxylated trimethylolpropane tri(meth)acrylate, and pentaerythritol Aliphatic (meth)acrylates such as pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tri(meth)acrylate, propoxylated pentaerythritol tri(meth)acrylate, ethoxylated propoxylated pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated propoxylated pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, and dipentaerythritol hexa(meth)acrylate; aromatic epoxy (meth)acrylates such as bisphenol-type epoxy (meth)acrylate, phenol novolac-type epoxy (meth)acrylate, and cresol novolac-type epoxy (meth)acrylate;

[0073] The content of the monofunctional (meth)acrylate may be, for example, from 0 to 60 mass %, from 0 to 50 mass %, or from 0 to 40 mass %, based on the total mass of the component (A1-1).

[0074] The content of the polyfunctional (difunctional or higher) (meth)acrylate may be, for example, 40 to 100 mass%, 50 to 100 mass%, or 60 to 100 mass%, based on the total mass of the component (A1-1), from the viewpoint of achieving both the effect of reducing connection resistance and the suppression of particle flow.

[0075] The component (A1-1) may contain, in addition to the (meth)acrylate compound, other radically polymerizable compounds. Examples of other radically polymerizable compounds include maleimide compounds, vinyl ether compounds, allyl compounds, styrene derivatives, acrylamide derivatives, and nadimide derivatives. The content of the other radically polymerizable compounds may be, for example, 0 to 40 mass% based on the total mass of the component (A1-1).

[0076] --(A1-2): Cationic polymerizable compound From the viewpoint of further improving the effect of reducing connection resistance and achieving more excellent connection reliability, the component (A1-2) may be a compound having a cyclic ether group. Among compounds having a cyclic ether group, when at least one selected from the group consisting of epoxy compounds and oxetane compounds is used, the effect of reducing connection resistance tends to be further improved.

[0077] The epoxy compound can be any compound having an epoxy group without any particular limitation. The number of epoxy groups in one molecule of the epoxy compound may be one or more. Examples of epoxy compounds that can be used include epoxy resins derived from bisphenol A and epichlorohydrin, and epoxy compounds having alicyclic epoxy groups. Commercially available epoxy compounds include bisphenol A epoxy resins such as YL-980 (trade name, manufactured by Mitsubishi Chemical Corporation) and jER9007 (trade name, manufactured by Mitsubishi Chemical Corporation), and alicyclic epoxy compounds such as EHPE3150, EHPE3150CE, CEL (Celloxide) 8010, CEL (Celloxide) 2021P, and CEL (Celloxide) 2081 (trade names, manufactured by Daicel Corporation). These compounds may be used alone or in combination.

[0078] The oxetane compound can be used without any particular limitation as long as it is a compound having an oxetanyl group. The number of oxetanyl groups in one molecule of the oxetane compound may be one or two or more. Commercially available oxetane compounds include, for example, ETERNACOLL OXBP (trade name, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl, manufactured by Ube Industries, Ltd.), OXSQ, OXT-121, OXT-221, OXT-101, and OXT-212 (trade names, manufactured by Toagosei Co., Ltd.). These compounds may be used alone or in combination.

[0079] -(A2): Curing agent for photocurable compounds The component (A2) is, for example, a photopolymerization initiator. The component (A2) may be, for example, a photoradical polymerization initiator (hereinafter sometimes referred to as "component (A2-1)") or a photocationic polymerization initiator (hereinafter sometimes referred to as "component (A2-2)"). The component (A2) may be selected depending on the type of component (A1). When the component (A1) is a radically polymerizable compound, a photoradical polymerization initiator may be used as the component (A2), and when the component (A1) is a cationically polymerizable compound, a photocationic polymerization initiator may be used as the component (A2).

[0080] --(A2-1): Photoradical polymerization initiator The component (A2-1) is a compound that generates radicals when irradiated with light having a wavelength in the range of 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, and more preferably light having a wavelength of 365 nm (e.g., ultraviolet light).The component (A2-1) may be used alone or in combination of two or more types.

[0081] The component (A2-1) decomposes in the presence of light to generate free radicals. In other words, the component (A2-1) is a compound that generates radicals upon application of external light energy. The component (A2-1) may be a compound having an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyl dimethyl ketal structure, an α-hydroxyalkylphenone structure, or the like. From the viewpoints of easily achieving a desired melt viscosity and achieving a more effective reduction in connection resistance, the component (A2-1) may be a compound having at least one structure selected from the group consisting of an oxime ester structure, an α-aminoalkylphenone structure, and an acylphosphine oxide structure.

[0082] Specific examples of compounds having an oxime ester structure include 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-o-benzoyloxime, 1,3-diphenylpropanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(o-benzoyl)oxime, 1,2-octanedione, 1-[4-(phenylthio)phenyl-, 2-(o-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(o-acetyloxime), and the like.

[0083] Specific examples of compounds having an α-aminoalkylphenone structure include 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-morpholinophenyl)-butanone-1, and the like.

[0084] Specific examples of compounds having an acylphosphine oxide structure include bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0085] The content of the component (A2-1) may be, for example, 0.1 to 10 parts by mass, 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass per 100 parts by mass of the component (A1-1) in order to suppress the flow of the conductive particles.

[0086] --(A2-2): Photocationic polymerization initiator The component (A2-2) is a photopolymerization initiator that generates cationic species upon irradiation with light having a wavelength in the range of 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, and more preferably light having a wavelength of 365 nm (e.g., ultraviolet light). The component (A2-2) may be used alone or in combination with multiple types.

[0087] Examples of the component (A2-2) include onium salts such as aromatic diazonium salts, aromatic sulfonium salts, aliphatic sulfonium salts, aromatic iodonium salts, phosphonium salts, pyridinium salts, and selenonium salts; complex compounds such as metal arene complexes and silanol / aluminum complexes; benzoin tosylate; and o-nitrobenzyl tosylate. Among these, sulfonium salts such as aromatic sulfonium salts and aliphatic sulfonium salts, iodonium salts such as aromatic iodonium salts, and iron-arene complexes are particularly likely to provide good reactivity due to their high cationic species generation efficiency. When the component (A2-2) is an onium salt, better reactivity is likely to be achieved when the counter anion is hexafluoroantimonate, hexafluorophosphonate, tetrafluoroborate, tetrakis(pentafluorophenyl)borate, or the like.

[0088] The component (A2-2) may also be a compound that generates an organic acid upon light irradiation or heating, such as a triarylsilyl peroxide derivative, an acylsilane derivative, an α-sulfonyloxyketone derivative, an α-hydroxymethylbenzoin derivative, a nitrobenzyl ester derivative, or an α-sulfonylacetophenone derivative. Specifically, from the viewpoint of acid generation efficiency upon light irradiation or heating, the CPI series manufactured by San-Apro Co., Ltd., the Adeka Optomer SP series manufactured by Asahi Denka Kogyo Co., Ltd., the Adeka Opton CP series manufactured by Asahi Denka Kogyo Co., Ltd., the Cyracure UVI series manufactured by Union Carbide, or the IRGACURE series manufactured by Ciba Specialty Chemicals is preferably used. Furthermore, if necessary, a known singlet sensitizer or triplet sensitizer, such as an anthracene or thioxanthone derivative, may be used in combination.

[0089] The content of the component (A2-2) may be, for example, 0.1 to 10 parts by mass, 0.3 to 7 parts by mass, or 0.5 to 5 parts by mass per 100 parts by mass of the component (A1-2) in order to suppress the flow of the conductive particles.

[0090] When adhesive component 5 contains component (B) in addition to a cured product of component (A), it is preferable to use a component (A) having a curing property different from that of component (B). For example, when adhesive component 5 contains component (B) having cation curing properties, it is preferable to use components (A1-1) and (A2-1) as component (A), and when adhesive component 5 contains component (B) having radical curing properties, it is preferable to use components (A1-2) and (A2-2) as component (A).

[0091] The content of the cured product of component (A) may be 1% by mass or more, 5% by mass or more, or 10% by mass or more, based on the total amount of adhesive components in the first adhesive layer, from the viewpoint of suppressing the flow of conductive particles. The content of the cured product of component (A) may be 50% by mass or less, 40% by mass or less, or 30% by mass or less, based on the total amount of adhesive components in the first adhesive layer, from the viewpoint of achieving low resistance in low-pressure mounting. From these viewpoints, the content of the cured product of component (A) may be, for example, 1 to 50% by mass, 5 to 40% by mass, or 10 to 30% by mass, based on the total amount of adhesive components in the first adhesive layer. The content of component (A) (based on the total amount of components other than conductive particles in the composition) in the composition for forming first adhesive layer 2 (the first adhesive composition described below) may be within the above-mentioned range.

[0092] (B): Thermosetting component Component (B) is a component that can flow when the circuit is connected, such as an uncured curable resin component. Component (B) is not particularly limited as long as it is a component that is cured by heat (such as a resin component). Component (B) includes, for example, a thermosetting compound (hereinafter sometimes referred to as "component (B1)") and a curing agent (latent curing agent) for the thermosetting compound (hereinafter sometimes referred to as "component (B2)").

[0093] -(B1):Thermosetting compound Component (B1) is a compound that reacts and crosslinks when heated in the presence of component (B2). Component (B1) may be, for example, a radically polymerizable compound or a cationically polymerizable compound. The radically polymerizable compound may be any of the compounds detailed above for component (A1-1), and the details (preferred compounds, content ratio, etc.) are the same as for component (A1-1). Similarly, the cationically polymerizable compound may be any of the compounds detailed above for component (A1-2), and the details (preferred compounds, content ratio, etc.) are the same as for component (A1-2). Component (B1) may be used alone or in combination.

[0094] -(B2): Curing agent for thermosetting compounds The component (B2) is, for example, a thermal polymerization initiator. The component (B2) may be, for example, a thermal radical polymerization initiator (hereinafter sometimes referred to as "component (B2-1)") or a thermal cationic polymerization initiator (hereinafter sometimes referred to as "component (B2-2)"). The component (B2) may be selected depending on the type of component (B1). When the component (B1) is a radically polymerizable compound, a thermal radical polymerization initiator may be used as the component (B2), and when the component (B1) is a cationic polymerizable compound, a thermal cationic polymerization initiator may be used as the component (B2).

[0095] --(B2-1): Thermal radical polymerization initiator The component (B2-1) decomposes upon heating to generate free radicals. That is, the component (B2-1) is a compound that generates radicals upon application of external thermal energy. The component (B2-1) can be selected from conventionally known organic peroxides and azo compounds. The component (B2-1) may be an organic peroxide from the viewpoint of further improving the effect of suppressing the flow of conductive particles and the effect of suppressing peeling after transfer. From the viewpoint of improving stability, reactivity, and compatibility, the component (B2-1) may be an organic peroxide having a one-minute half-life temperature of 90 to 175°C and a weight-average molecular weight of 180 to 1,000. When the one-minute half-life temperature of the organic peroxide is within the above range, the storage stability tends to be even better, and sufficiently high radical polymerization property can be obtained, enabling curing in a short period of time.

[0096] Specific examples of the component (B2-1) include 1,1,3,3-tetramethylbutyl peroxyneodecanoate, di(4-t-butylcyclohexyl) peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, cumyl peroxyneodecanoate, dilauroyl peroxide, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, t-hexyl peroxyneodecanoate, t-butyl peroxyneodecanoate, and t-butyl peroxyneodecanoate. peroxypivalate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, t-hexylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylhexanoate, t-butylperoxyneoheptanoate, t-amylperoxy-2-ethylhexanoate, di-t-butylperoxyhexahydroterephthalate, t-amylperoxy-3,5 ,5-trimethylhexanoate, 3-hydroxy-1,1-dimethylbutylperoxyneodecanoate, t-amylperoxyneodecanoate, di(3-methylbenzoyl) peroxide, dibenzoyl peroxide, di(4-methylbenzoyl) peroxide, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2, organic peroxides such as 5-dimethyl-2,5-di(3-methylbenzoylperoxy)hexane, t-butylperoxy-2-ethylhexyl monocarbonate, t-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butyl peroxybenzoate, dibutyl peroxytrimethyl adipate, t-amyl peroxy normal octoate, t-amyl peroxy isononanoate, and t-amyl peroxybenzoate;Examples of azo compounds include 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(1-acetoxy-1-phenylethane), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 4,4'-azobis(4-cyanovaleric acid), and 1,1'-azobis(1-cyclohexanecarbonitrile);

[0097] From the viewpoint of achieving excellent rapid curing properties, and further improving the effect of suppressing the flow of conductive particles and the effect of suppressing peeling after transfer, the content of the component (B2-1) may be, for example, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass relative to 100 parts by mass of the radical polymerizable compound contained as the component (B1).

[0098] --(B2-2): Thermal cationic polymerization initiator The component (B2-2) is a thermal polymerization initiator (thermal latent cation generator) that generates an acid or the like upon heating to initiate polymerization. The component (B2-2) may be a salt compound composed of a cation and an anion. Examples of the component (B2-2) include BF4 - , BR4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups), PF6 - , SbF6 - , AsF6 - and onium salts such as sulfonium salts, phosphonium salts, ammonium salts, diazonium salts, iodonium salts, and anilinium salts having anions such as those listed above. These may be used alone or in combination of two or more.

[0099] From the viewpoint of rapid curing, the component (B2-2) may be, for example, a salt compound having an anion containing boron as a constituent element. Examples of such salt compounds include BF4 - or BR4 - (R represents a phenyl group substituted with two or more fluorine atoms or two or more trifluoromethyl groups). An anion containing boron as a constituent element is BR4- and more specifically, tetrakis(pentafluorophenyl)borate.

[0100] From the viewpoint of storage stability, the component (B2-2) may be a sulfonium salt or an ammonium salt.

[0101] The sulfonium salt may be, for example, a salt compound having a cation represented by the following formula (II): [ka]

[0102] In formula (II), R 5 and R 6 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing a substituted or unsubstituted aromatic hydrocarbon group, and R 7 represents an alkyl group having 1 to 6 carbon atoms.

[0103] The salt compound having a cation represented by formula (II) may be an aromatic sulfonium salt compound from the viewpoint of achieving both storage stability and low-temperature activity. 5 and R 6 At least one of the above may be an organic group containing a substituted or unsubstituted aromatic hydrocarbon group. The anion in the salt compound having the cation represented by formula (II) may be an anion containing antimony as a constituent element, such as hexafluoroantimonate (hexafluoroantimonic acid).

[0104] Specific examples of compounds having a cation represented by formula (II) include 1-naphthylmethyl-p-hydroxyphenylsulfonium hexafluoroantimonate (manufactured by Sanshin Chemical Industry Co., Ltd., SI-60 base agent).

[0105] The ammonium salt may be, for example, a salt compound having a cation represented by the following formula (III):

[0106] [ka]

[0107] In formula (III), R 8 and R 9 each independently represents a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, or an organic group containing a substituted or unsubstituted aromatic hydrocarbon group, and R 10 and R 11 are each independently an alkyl group having 1 to 6 carbon atoms.

[0108] The salt compound having a cation represented by formula (III) may be, for example, an anilinium salt compound, since it has resistance to substances that can cause curing inhibition in cationic curing. 8 and R 9 At least one of the groups may be an organic group containing a substituted or unsubstituted aromatic hydrocarbon group. Examples of the anilinium salt compound include N,N-dialkylanilinium salts such as N,N-dimethylanilinium salt and N,N-diethylanilinium salt. The anion in the salt compound having a cation represented by formula (III) may be an anion containing boron as a constituent element, such as tetrakis(pentafluorophenyl)borate.

[0109] The compound having the cation represented by formula (III) may be an anilinium salt having an anion containing boron as a constituent element. Commercially available products of such salt compounds include CXC-1821 (trade name, manufactured by King Industries).

[0110] From the viewpoint of ensuring the formability and curability of the first adhesive layer, the content of the (B2-2) component may be, for example, 0.1 to 20 parts by mass, 1 to 18 parts by mass, 3 to 15 parts by mass, or 5 to 12 parts by mass relative to 100 parts by mass of the cationically polymerizable compound contained as the (B1) component.

[0111] Component (B) is not limited to the combination of components (B1) and (B2). For example, when component (B1) contains the above-mentioned epoxy compound and / or oxetane compound, component (B2) may be a known amine-based curing agent or imidazole-based curing agent.

[0112] From the viewpoint of achieving better electrical conductivity between opposing electrodes, component (B) may be a thermocationically curable component and component (A) may be a photoradical curable component. More specifically, when component (B) contains at least one selected from the group consisting of epoxy compounds and oxetane compounds as a cationically polymerizable compound and component (A) contains a (meth)acrylate compound as a radically polymerizable compound, the electrical conductivity between opposing electrodes tends to be even better.

[0113] The content of the (B) component may be, for example, 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total amount of adhesive components in the first adhesive layer, from the viewpoint of ensuring the curability of the first adhesive layer. The content of the (B) component may be, for example, 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total amount of adhesive components in the first adhesive layer, from the viewpoint of ensuring the formability of the first adhesive layer. From these viewpoints, the content of the (B) component may be, for example, 5 to 70% by mass, 10 to 60% by mass, 15 to 50% by mass, or 20 to 40% by mass, based on the total amount of adhesive components in the first adhesive layer. The content of the (B) component in the composition for forming the first adhesive layer 2 (the first adhesive composition described below) (based on the total amount of components other than the conductive particles in the composition) may be in the same range as above. The total amount of component (B) in the circuit-connecting adhesive (based on the total amount of adhesive components in the circuit-connecting adhesive) may also be within the above range.

[0114] (C): Other ingredients The first adhesive layer 2 may further contain components (other components) other than the components described above. Examples of the other components include a thermoplastic resin, a coupling agent, and a filler.

[0115] As the thermoplastic resin, a resin that functions as a film-forming component can be used. Examples of the thermoplastic resin include phenoxy resin, polyester resin, polyamide resin, polyurethane resin, polyester urethane resin, acrylic rubber, and epoxy resin (solid at 25°C). These may be used alone or in combination of two or more. The use of a thermoplastic resin improves film formability. Among these, when the thermoplastic resin is a phenoxy resin, film formability is more likely to be improved.

[0116] From the viewpoint of resin removal properties during mounting, the weight average molecular weight (Mw) of the thermoplastic resin may be, for example, 5,000 to 200,000, 10,000 to 100,000, 20,000 to 80,000, or 40,000 to 60,000. Mw refers to a value measured by gel permeation chromatography (GPC) and converted using a calibration curve based on standard polystyrene.

[0117] The content of the thermoplastic resin may be 1% by mass or more, 5% by mass or more, 10% by mass or more, or 20% by mass or more, and may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total amount of adhesive components in the first adhesive layer. The content of the thermoplastic resin in the composition for forming the first adhesive layer 2 (the first adhesive composition described below) (based on the total amount of components other than the conductive particles in the composition) may be the same as the above range. The total amount of the thermoplastic resin in the circuit-connecting adhesive (based on the total amount of adhesive components in the circuit-connecting adhesive) may also be the same as the above range.

[0118] Examples of coupling agents include silane coupling agents having organic functional groups such as (meth)acryloyl groups, mercapto groups, amino groups, imidazole groups, and epoxy groups; silane compounds such as tetraalkoxysilane; tetraalkoxytitanate derivatives; and polydialkyltitanate derivatives. These may be used singly or in combination. The inclusion of a coupling agent in the first adhesive layer 2 can further improve adhesion. The coupling agent may be, for example, a silane coupling agent. The content of the coupling agent may be 0.1 to 10 mass% based on the total amount of adhesive components in the first adhesive layer. The content of the coupling agent in the composition for forming the first adhesive layer 2 (the first adhesive composition described below) (based on the total amount of components other than the conductive particles in the composition) may be within the above-mentioned range. The total amount of the coupling agent in the circuit-connecting adhesive (based on the total amount of adhesive components in the circuit-connecting adhesive) may also be within the above-mentioned range.

[0119] Examples of the filler include non-conductive fillers (e.g., non-conductive particles). The filler may be either an inorganic filler or an organic filler. Examples of inorganic fillers include inorganic fine particles such as metal oxide fine particles, such as silica fine particles, alumina fine particles, silica-alumina fine particles, titania fine particles, and zirconia fine particles; and metal nitride fine particles. Examples of organic fillers include organic fine particles, such as silicone fine particles, methacrylate-butadiene-styrene fine particles, acrylic-silicone fine particles, polyamide fine particles, and polyimide fine particles. These may be used alone or in combination. The content of the filler may be 0.1 to 10 mass% based on the total amount of adhesive components in the first adhesive layer. The content of the filler in the composition for forming the first adhesive layer 2 (the first adhesive composition described below) (based on the total amount of components other than the conductive particles in the composition) may be the same as the above range. The total amount of the filler in the circuit-connecting adhesive (based on the total amount of adhesive components in the circuit-connecting adhesive) may also be the same as the above range.

[0120] The first adhesive layer 2 may further contain other additives such as softeners, accelerators, anti-degradants, colorants, flame retardants, and thixotropic agents. The content (total amount) of the other additives may be, for example, 0.1 to 10 mass% based on the total amount of adhesive components in the first adhesive layer. The content (based on the total amount of components other than the conductive particles in the composition) of the other additives in the composition for forming the first adhesive layer 2 (the first adhesive composition described below) may be the same as the above range. The total amount of the other additives in the circuit-connecting adhesive (based on the total amount of adhesive components in the circuit-connecting adhesive) may also be the same as the above range.

[0121] The thickness D1 of the first adhesive layer 2 may be, for example, 5 μm or less. The thickness D1 of the first adhesive layer 2 may be 4.5 μm or less or 4.0 μm or less. By having the thickness D1 of the first adhesive layer 2 be 5 μm or less, conductive particles can be captured more efficiently during circuit connection. The thickness D1 of the first adhesive layer 2 may be, for example, 0.1 μm or more, 0.5 μm or more, or 0.7 μm or more. The thickness D1 of the first adhesive layer 2 can be determined, for example, by sandwiching an adhesive film between two pieces of glass (thickness: approximately 1 mm), casting a resin composition consisting of 100 g of bisphenol A epoxy resin (trade name: jER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (trade name: Epomount Curing Agent, manufactured by Refine Tech Co., Ltd.), polishing the cross section using a polishing machine, and measuring the thickness using a scanning electron microscope (SEM, trade name: SE-8020, manufactured by Hitachi High-Tech Science Corporation). 1, when a portion of the conductive particles 4 is exposed from the surface of the first adhesive layer 2 (for example, protruding toward the second adhesive layer 3), the distance from the surface 2a of the first adhesive layer 2 opposite the second adhesive layer 3 to the boundary S between the first adhesive layer 2 and the second adhesive layer 3, which is located in the space between adjacent conductive particles 4,4 (the distance indicated by D1 in FIG. 1), is the thickness of the first adhesive layer 2, and the exposed portions of the conductive particles 4 are not included in the thickness of the first adhesive layer 2. The length of the exposed portions of the conductive particles 4 may be, for example, 0.1 μm or more and 5 μm or less.

[0122] (Second adhesive layer) The second adhesive layer 3 contains, for example, a thermosetting component. The compounds detailed as component (B) can be used as the thermosetting component. The details (preferred compounds, content ratio, etc.) are the same as those for component (B). The thermosetting component (first thermosetting component) contained in the first adhesive layer 2 and the thermosetting component (second thermosetting component) contained in the second adhesive layer 3 may be the same as or different from each other.

[0123] The content of the thermosetting component may be 5% by mass or more, 10% by mass or more, 15% by mass or more, or 20% by mass or more, based on the total mass of the second adhesive layer, from the viewpoint of maintaining reliability. The content of the thermosetting component may be 70% by mass or less, 60% by mass or less, 50% by mass or less, or 40% by mass or less, based on the total mass of the second adhesive layer, from the viewpoint of preventing resin seepage problems in a reel, which is one embodiment of the supply form. From these viewpoints, the content of the thermosetting component may be, for example, 5 to 70% by mass, 10 to 60% by mass, 15 to 50% by mass, or 20 to 40% by mass, based on the total mass of the second adhesive layer. The content of the thermosetting component (based on the total mass of the composition) in the composition for forming second adhesive layer 3 (the second adhesive composition described below) may be in the same range as above.

[0124] The second adhesive layer 3 may further contain other components in the first adhesive layer 2. Details of the other components are the same as those of the first adhesive layer 2.

[0125] The content of the thermoplastic resin may be 1 mass % or more, 5 mass % or more, or 10 mass % or more, and may be 80 mass % or less, 60 mass % or less, or 40 mass % or less, based on the total mass of the second adhesive layer. The content of the thermoplastic resin in the composition for forming the second adhesive layer 3 (the second adhesive composition described below) (based on the total mass of the composition) may be in the same range as above.

[0126] The content of the coupling agent may be 0.1 to 10% by mass based on the total mass of the second adhesive layer. The content of the coupling agent in the composition for forming the second adhesive layer 3 (the second adhesive composition described below) (based on the total mass of the composition) may be in the same range as above.

[0127] The content of the filler may be 1 mass % or more, 5 mass % or more, or 10 mass % or more, and may be 70 mass % or less, 50 mass % or less, or 30 mass % or less, based on the total mass of the second adhesive layer. The content of the filler in the composition for forming the second adhesive layer 3 (the second adhesive composition described below) (based on the total mass of the composition) may be the same as the above range.

[0128] The content of the other additives may be, for example, 0.1 to 10% by mass based on the total mass of the second adhesive layer. The content of the other additives in the composition for forming the second adhesive layer 3 (the second adhesive composition described below) (based on the total mass of the composition) may be the same as the above range.

[0129] The content of the conductive particles in the second adhesive layer 3 is, for example, 1% by mass or less, and may be 0% by mass, based on the total mass of the second adhesive layer. That is, the second adhesive layer 3 does not need to contain conductive particles. The content of the conductive particles (based on the total mass of the composition) in the composition for forming the second adhesive layer 3 (the second adhesive composition described below) may be the same as the above range.

[0130] The thickness D2 of the second adhesive layer 3 may be appropriately set depending on the height of the electrodes of the circuit components to be bonded, etc. The thickness D2 of the second adhesive layer 3 may be 5 μm or more or 7 μm or more, and 15 μm or less or 11 μm or less, from the viewpoint of being able to sufficiently fill the space between the electrodes and seal the electrodes, thereby obtaining better connection reliability. The thickness D2 of the second adhesive layer 3 can be determined, for example, by a method similar to the method for measuring the thickness D1 of the first adhesive layer 2. Furthermore, when a portion of the conductive particles 4 is exposed from the surface of the first adhesive layer 2 (for example, protruding toward the second adhesive layer 3), the thickness of the second adhesive layer 3 is the distance (distance D2 in FIG. 1 ) from the surface 3 a of the second adhesive layer 3 opposite the first adhesive layer 2 side to the boundary S between the first adhesive layer 2 and the second adhesive layer 3, which is located in the space between adjacent conductive particles 4, 4.

[0131] The thickness of the adhesive film 1 (the sum of the thicknesses of all layers constituting the adhesive film 1; in Figure 1, the sum of the thickness D1 of the first adhesive layer 2 and the thickness D2 of the second adhesive layer 3) may be, for example, 5 μm or more or 8 μm or more, and may be 30 μm or less or 20 μm or less.

[0132] The adhesive film 1 can be produced, for example, by a method comprising the steps of: irradiating a layer made of a first adhesive composition containing the above-described conductive particles, a photocurable component, a thermosetting component, and other components with light to form a first adhesive layer 2 (first step); and laminating a second adhesive layer 3 made of a second adhesive composition containing the above-described thermosetting component and other components on the first adhesive layer 2 (second step). If the first adhesive composition does not contain a photocurable component in the first step, light irradiation in the first step need not be performed.

[0133] In the first step, for example, the first adhesive composition is first dissolved or dispersed in an organic solvent by stirring, mixing, kneading, or the like to prepare a varnish composition (varnish-like first adhesive composition). The varnish composition is then applied to a release-treated substrate using a knife coater, roll coater, applicator, comma coater, die coater, or the like, and the organic solvent is then volatilized by heating to form a layer of the first adhesive composition on the substrate. The thickness of the first adhesive layer can be adjusted by adjusting the amount of varnish composition applied. Next, if the first adhesive composition contains a photocurable component, the layer of the first adhesive composition is irradiated with light to cure the photocurable component in the layer. Through these operations, a first adhesive layer 2 is formed on the substrate, and a first adhesive film comprising the first adhesive layer 2 is obtained.

[0134] The organic solvent used in preparing the varnish composition is not particularly limited as long as it has the property of being able to uniformly dissolve or disperse each component. Examples of such organic solvents include toluene, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, propyl acetate, butyl acetate, etc. These organic solvents can be used alone or in combination of two or more. The stirring, mixing, or kneading in preparing the varnish composition can be performed using, for example, a mixer, a grinder, a three-roll mill, a ball mill, a bead mill, a homodisper, etc.

[0135] The substrate is not particularly limited as long as it has heat resistance sufficient to withstand the heating conditions required for volatilizing the organic solvent. Examples of such substrates include substrates (e.g., films) made of oriented polypropylene (OPP), polyethylene terephthalate (PET), polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, polyolefin, polyacetate, polycarbonate, polyphenylene sulfide, polyamide, polyimide, cellulose, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, synthetic rubber, and liquid crystal polymer.

[0136] The heating conditions for volatilizing the organic solvent from the varnish composition applied to the substrate can be appropriately set depending on the organic solvent used, etc. The heating conditions may be, for example, 40 to 120°C for 0.1 to 10 minutes.

[0137] A portion of the solvent may remain unremoved in the first adhesive layer 2. The content of the solvent in the first adhesive layer 2 may be, for example, 10 mass % or less based on the total mass of the first adhesive layer.

[0138] For the light irradiation in the curing step, it is preferable to use irradiation light (for example, ultraviolet light) having a wavelength in the range of 150 to 750 nm. Light irradiation can be carried out using, for example, a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, etc. The cumulative light amount of the light irradiation can be set appropriately, but is, for example, 500 to 3000 mJ / cm. 2 It may be.

[0139] The second step is a step of laminating a second adhesive layer 3 on the first adhesive layer 2. In the second step, for example, the second adhesive layer 3 is formed on the substrate in the same manner as the first step, except that the second adhesive composition is used instead of the first adhesive composition and light irradiation is not performed, and then the obtained second adhesive film and the first adhesive film are bonded together to laminate the second adhesive layer 3 on the first adhesive layer 2.

[0140] Examples of methods for bonding the first adhesive film and the second adhesive film include hot pressing, roll lamination, vacuum lamination, etc. Lamination can be carried out under temperature conditions of 0 to 80°C, for example.

[0141] In the second step, for example, a second adhesive layer 3 may be laminated on the first adhesive layer 2 by applying a varnish-like second adhesive composition onto the first adhesive layer 2 and volatilizing the organic solvent.

[0142] A portion of the solvent may remain unremoved in the second adhesive layer 3. The content of the solvent in the second adhesive layer 3 may be, for example, 10 mass % or less based on the total mass of the second adhesive layer.

[0143] Although the circuit connecting adhesive of this embodiment has been described above, the present invention is not limited to the above embodiment.

[0144] The circuit connection adhesive may be, for example, a single-layer adhesive film consisting of only the above-mentioned first adhesive layer, or may be an adhesive film consisting of three or more layers including two layers, the above-mentioned first adhesive layer and second adhesive layer.

[0145] <Connection structure and method for manufacturing the same> Hereinafter, a connection structure (circuit connection structure) using the above-mentioned adhesive film for circuit connection 1 as the circuit connecting material and a method for producing the same will be described.

[0146] Fig. 4 is a schematic cross-sectional view showing one embodiment of a connection structure. As shown in Fig. 4, a connection structure 10 includes a first circuit board 11 and a first circuit member 13 having a first electrode 12 formed on a main surface 11a of the first circuit board 11, a second circuit board 14 and a second circuit member 16 having a second electrode 15 formed on a main surface 14a of the second circuit board 14, and a circuit connection portion 17 disposed between the first circuit member 13 and the second circuit member 16 and electrically connecting the first electrode 12 and the second electrode 15 to each other.

[0147] The first circuit member 13 and the second circuit member 16 may be the same or different. The first circuit member 13 and the second circuit member 16 may be a glass or plastic substrate on which circuit electrodes are formed; a printed wiring board; a ceramic wiring board; a flexible wiring board; a semiconductor element (IC chip) such as a driving IC; or the like. The first circuit board 11 and the second circuit board 14 may be formed from an inorganic material such as a semiconductor, glass, or ceramic; an organic material such as polyimide or polycarbonate; or a composite material such as glass / epoxy. The first circuit board 11 may be a plastic substrate (a plastic substrate made of an organic material such as polyimide, polycarbonate, polyethylene terephthalate, or cycloolefin polymer). The first circuit member 13 may be, for example, a plastic substrate on which circuit electrodes are formed (a plastic substrate with circuit electrodes). The plastic substrate with circuit electrodes may be a plastic substrate on which a display area is formed by, for example, a pixel driving circuit such as an organic TFT or a plurality of organic EL elements R, G, and B are regularly arranged in a matrix. The second circuit member 16 may be, for example, a semiconductor element (IC chip) such as a driving IC.

[0148] The first electrode 12 and the second electrode 15 may be electrodes containing metals such as gold, silver, tin, ruthenium, rhodium, palladium, osmium, iridium, platinum, copper, aluminum, molybdenum, and titanium, or oxides such as indium tin oxide (ITO), indium zinc oxide (IZO), and indium gallium zinc oxide (IGZO). The first electrode 12 and the second electrode 15 may be electrodes formed by laminating two or more of these metals, oxides, and the like. An electrode formed by laminating two or more of these metals, oxides, and the like may have two or more layers, or may have three or more layers. When the first circuit member 13 is a plastic substrate, the first electrode 12 may be an electrode having titanium on its connection surface. Here, the connection surface refers to the surface (the outermost surface of the electrode) that comes into contact with the circuit connection adhesive 1 during the production of the connection structure 10. An electrode having titanium on its connection surface may have an oxide coating (titanium oxide coating) formed on its outermost surface by oxidizing the titanium. The first electrode 12 and the second electrode 15 may be circuit electrodes or bump electrodes. At least one of the first electrode 12 and the second electrode 15 may be a bump electrode. Figure 4 shows an embodiment in which the first electrode 12 is a circuit electrode and the second electrode 15 is a bump electrode.

[0149] The circuit connection portion 17 includes a cured product of the adhesive film 1 described above. The circuit connection portion 17 may be made of a cured product of the adhesive film 1 described above. The circuit connection portion 17 has, for example, a first region 18 located on the first circuit member 13 side in the direction in which the first circuit member 13 and the second circuit member 16 face each other (hereinafter referred to as the "facing direction") and made of a cured product derived from the first adhesive layer described above (e.g., a cured composition including a cured product of a photocurable component and a cured product of a thermosetting component), a second region 19 located on the second circuit member 16 side in the facing direction and made of a cured product derived from the second adhesive layer described above (e.g., a cured composition including a cured product of a thermosetting component), and conductive particles 4 interposed at least between the first electrode 12 and the second electrode 15 to electrically connect the first electrode 12 and the second electrode 15 to each other. As shown in FIG. 4, the circuit connection portion 17 does not have to have two distinct regions between the first region 18 and the second region 19, but may have a single region formed by a mixture of the cured material derived from the first adhesive layer and the cured material derived from the second adhesive layer.

[0150] Examples of the connection structure include a flexible organic electroluminescent color display (organic EL display) in which a plastic substrate on which organic EL elements are regularly arranged is connected to a drive circuit element that is a driver for displaying images, and a touch panel in which a plastic substrate on which organic EL elements are regularly arranged is connected to a position input element such as a touchpad. The connection structure can be applied to various monitors such as smartphones, tablets, televisions, vehicle navigation systems, and wearable devices; furniture; home appliances; and daily necessities.

[0151] Figure 5 is a schematic cross-sectional view showing one embodiment of a method for manufacturing a connection structure. Figures 5(a) and 5(b) are schematic cross-sectional views showing each step. As shown in Figure 5, the method for manufacturing a connection structure 10 includes the steps of interposing the above-mentioned adhesive film 1 between a first circuit member 13 having a first electrode 12 and a second circuit member 16 having a second electrode 15, and thermocompression bonding the first circuit member 13 and the second circuit member 16 to electrically connect the first electrode 12 and the second electrode 15 to each other.

[0152] Specifically, as shown in FIG. 5(a), first, a first circuit member 13 including a first circuit board 11 and a first electrode 12 formed on the main surface 11a of the first circuit board 11, and a second circuit member 16 including a second circuit board 14 and a second electrode 15 formed on the main surface 14a of the second circuit board 14 are prepared.

[0153] Next, the first circuit member 13 and the second circuit member 16 are arranged so that the first electrode 12 and the second electrode 15 face each other, and the adhesive film 1 is placed between the first circuit member 13 and the second circuit member 16. For example, as shown in FIG. 5( a), the adhesive film 1 is laminated onto the first circuit member 13 so that the first adhesive layer 2 faces the main surface 11a of the first circuit board 11. Next, the second circuit member 16 is placed on the first circuit member 13 to which the adhesive film 1 has been laminated so that the first electrode 12 on the first circuit board 11 and the second electrode 15 on the second circuit board 14 face each other.

[0154] 5(b), the first circuit member 13 and the second circuit member 16 are heated while being pressed against each other in the thickness direction, thereby thermocompressing the first circuit member 13 and the second circuit member 16 together. During this process, as indicated by the arrows in FIG. 5(b), the second adhesive layer 3 contains a flowable, uncured thermosetting component, so that it flows to fill the gaps between the second electrodes 15 and is cured by the heating. As a result, the first electrode 12 and the second electrode 15 are electrically connected to each other via the conductive particles 4, and the first circuit member 13 and the second circuit member 16 are bonded to each other, thereby obtaining the connection structure 10 shown in FIG. 4. When an adhesive film having a first adhesive layer 2 (an adhesive layer at least a portion of which is cured by light irradiation) containing a cured product of a photocurable component is used as the adhesive film 1, the conductive particles 4 hardly flow during the above-mentioned thermocompression bonding, and the conductive particles are efficiently captured between the opposing electrodes, thereby further reducing the connection resistance between the opposing first electrode 12 and second electrode 15.

[0155] The heating temperature for thermocompression bonding can be set appropriately, but may be, for example, 50 to 190°C. The pressure to be applied is not particularly limited as long as it does not damage the adherend, but in the case of COP mounting, for example, the equivalent surface area pressure for the bump electrode may be 0.1 to 50 MPa. In the case of COG mounting, for example, the equivalent surface area pressure for the bump electrode may be 10 to 100 MPa. The heating and pressurizing time may be in the range of 0.5 to 120 seconds. [Example]

[0156] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0157] <Preparing conductive particles> Conductive particles 1A to 8A were prepared, each having a base particle, a metal layer covering the surface of the base particle, and a core material disposed within the metal layer and elevating the outer surface of the metal layer. Details of conductive particles 1A to 8A are shown in Table 1. In Table 1, the thickness d1 is the thickness of the flat portion of the metal layer, and the length l1 is the length of the core material in the thickness direction of the metal layer. Furthermore, since the metal layer of conductive particle 5A has a two-layer structure consisting of a nickel layer (inner layer) and a palladium layer (outer layer), the thickness d1 of the metal layer of conductive particle 5A is the sum of the thickness of the nickel layer (110 nm) and the thickness of the palladium layer (26 nm).

[0158] [Table 1]

[0159] <Preparation of the first adhesive layer and the second adhesive layer> (Material preparation) The materials shown below were used in producing the first adhesive layer and the second adhesive layer.

[0160] [Conductive particles] Conductive particles 1A to 8A prepared above

[0161] [Cationic polymerizable compounds] CEL2021P (3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (alicyclic epoxy compound), manufactured by Daicel Corporation) OXT-221 (3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (oxetane compound), manufactured by Toagosei Co., Ltd.)

[0162] [Cationic photopolymerization initiator] CPI-310B (triarylsulfonium tetrakis(pentafluorophenyl)borate, manufactured by San-Apro Co., Ltd.)

[0163] [Thermal cationic polymerization initiator] CXC-1821 (N-(p-methoxybenzyl)-N,N-dimethylanilium tetrakis(pentafluorophenyl)borate, manufactured by King Industries)

[0164] [Radical polymerizable compounds] A-BPEF70T (ethoxylated fluorene di(meth)acrylate (bifunctional), manufactured by Shin-Nakamura Chemical Co., Ltd.), diluted with toluene to 70% non-volatile content by mass, was used. VR-90 (bisphenol A type epoxy (meth)acrylate (bifunctional) (vinyl ester resin), manufactured by Showa Denko K.K.)

[0165] [Photoradical polymerization initiator] Irgacure 907 (a compound with an α-aminoalkylphenone structure, manufactured by BASF)

[0166] [Thermoplastic resin] FX293 (biphenyl, fluorene-type phenoxy resin, weight average molecular weight: 45,000, glass transition temperature: 158°C, manufactured by Nippon Steel Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a non-volatile content of 40% by mass. YP-70 (bisphenol A and bisphenol F copolymer phenoxy resin, weight average molecular weight: 55,000, glass transition temperature: 70°C, manufactured by Nippon Steel Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a non-volatile content of 50% by mass. FX316 (bisphenol F-type phenoxy resin, weight average molecular weight: 52,000, glass transition temperature: 65°C, manufactured by Nippon Steel Chemical & Material Co., Ltd.), diluted with methyl ethyl ketone to a non-volatile content of 40% by mass.

[0167] [Coupling agent] SH-6040 (3-glycidoxypropyltrimethoxysilane, manufactured by Dow Corning Toray Co., Ltd.)

[0168] [Filling material] SE2050 (silica particles, manufactured by Admatechs Co., Ltd.)

[0169] (Preparation of First Adhesive Film (First Adhesive Layer)) The materials shown in Table 2 were mixed in the composition ratios shown in Table 2 (the values ​​in Table 2 indicate the non-volatile content), and then a composition was obtained. This was then coated onto a release-treated PET (polyethylene terephthalate) film while applying a magnetic field, and the organic solvent was dried with hot air at 70°C for 5 minutes to obtain a composition layer containing each component. The composition layer was coated so that the thickness after drying (the thickness of the part where the conductive particles were present) would be 3 to 4 μm. The composition layer was then irradiated with light (UV irradiation: metal halide lamp, cumulative light intensity: 1900 to 2300 mJ / cm). 2), and first adhesive films 1A to 8A (thickness: 2.0 μm) were obtained. Note that if the thickness of the first adhesive film is smaller than the thickness (diameter) of the conductive particles, measuring the layer thickness using a contact thickness meter will reflect the thickness of the conductive particles, and the thickness of the region where the conductive particles are present will be measured. Therefore, after producing a two-layer adhesive film for circuit connection in which the first adhesive layer and the second adhesive layer are laminated, the thickness of the first adhesive layer was measured to obtain the thickness of the first adhesive film. Specifically, the circuit connection adhesive film was sandwiched between two pieces of glass (thickness: approximately 1 mm) and a resin composition consisting of 100 g of bisphenol A type epoxy resin (product name: jER811, manufactured by Mitsubishi Chemical Corporation) and 10 g of a curing agent (product name: Epomount curing agent, manufactured by Refine Tech Co., Ltd.) was poured into the mold.The cross section was then polished using a polishing machine, and the thickness of the first adhesive layer located in the space between adjacent conductive particles was measured using a scanning electron microscope (SEM, product name: SE-8020, manufactured by Hitachi High-Tech Science Corporation).

[0170] [Table 2]

[0171] (Preparation of Second Adhesive Film (Second Adhesive Layer)) The materials shown in Table 3 were mixed in the composition ratios shown in Table 3 (the numbers in Table 3 indicate the non-volatile content), and then coated onto a release-treated PET (polyethylene terephthalate) film. The organic solvent and other organic solvents were dried off to obtain second adhesive films 1A to 2A containing each component. The second adhesive films were coated so that their thickness after drying would be 8 to 10 μm.

[0172] [Table 3]

[0173] <Examples 1 to 5 and Comparative Examples 1 to 3> (Preparation of adhesive film for circuit connection) The first adhesive film and second adhesive film prepared above were bonded together using a laminator at a temperature of 50 to 60°C in the combinations shown in Tables 4 and 5. In this way, adhesive films for circuit connection of Examples 1 to 5 and Comparative Examples 1 to 3 were prepared.

[0174] (Fabrication of connection structure) Using each of the adhesive films for circuit connection of Examples 1 to 5 and Comparative Examples 1 to 3, a connection structure was produced by the method described below.

[0175] [Preparing circuit components] As the first circuit component, a plastic circuit board with a Ti / Al / Ti circuit (thickness: 0.05 mm) was prepared, and as the second circuit component, an IC chip with gold bumps (0.9 mm × 20.3 mm, thickness: 0.3 mm, bump electrode size: 12 μm × 100 μm, space between bump electrodes (pitch): 24 μm, bump electrode thickness: 8 μm) was prepared.

[0176] [Fabrication of connection structure] The adhesive film for circuit connection was cut into a width of 2.0 mm, and the adhesive film for circuit connection was placed on the first circuit member so that the first adhesive layer and the first circuit member were in contact. Using a thermo-temporary pressure bonding device (LD-06, manufactured by Ohashi Manufacturing Co., Ltd.) consisting of a stage made of a ceramic heater and a tool (8 mm × 50 mm), the adhesive film was heated at 70 °C and 0.98 MPa (10 kgf / cm 2 The adhesive film was attached to the first circuit member by applying heat and pressure for 2 seconds under the conditions of 160°C and 30 MPa equivalent pressure on the bump electrode. The release film on the adhesive film opposite the first circuit member was then peeled off. The circuit electrodes of the first circuit member were aligned with the bump electrodes of the second circuit member, and then the second adhesive layer of the circuit connection adhesive film was attached to the second circuit member by applying heat and pressure for 5 seconds using an 8 mm x 45 mm heat tool with 50 μm thick Teflon (registered trademark) as a buffer material under the conditions of 160°C connection and 30 MPa equivalent pressure on the bump electrode. A connection structure was produced by the above operations.

[0177] (evaluation) [Evaluation 1: Measurement of the thickness d1 of the metal layer of the conductive particles and the length l1 of the ceramic core] The connection structure prepared above was used with a casting resin such as epoxy resin to prepare a casting sample. The casting sample was polished using a polishing machine (manufactured by Refine Tech Co., Ltd.) to prepare a cross-sectional sample that allowed the cross-section of the connection structure to be confirmed. The prepared cross-sectional sample was examined using a scanning electron microscope (SU8000, manufactured by Hitachi High-Tech Corporation) at a magnification of 15,000x, and the thickness d1 of the metal layer on the conductive particle and the length l1 of the ceramic core material were measured at three arbitrary points for three arbitrary conductive particles. The average values ​​of the nine measurements were calculated, and the values ​​shown in Table 1 above were confirmed.

[0178] [Evaluation 2: Measurement of the amount of conductive particles embedded in the titanium electrode] The cross-sectional sample prepared in Evaluation 1 was measured for the amount of conductive particles embedded in the titanium electrode using a scanning electron microscope (SU8000, manufactured by Hitachi High-Tech Corporation) set at a magnification of 50,000. The results are shown in Tables 4 and 5.

[0179] [Evaluation 3: Evaluation of electrical conductivity (connection resistance) The initial connection resistance (conduction resistance) of the connection structure prepared above was measured using a four-terminal method. For the measurement, a constant current (1 mA) was applied between the circuit electrode of the first circuit member and the bump electrode of the second circuit member (connection portion) of the connection structure using a constant current power supply R-6145 manufactured by Advantest Corporation. The potential difference at the connection portion during current application was measured using a digital multimeter (R-6557) manufactured by Advantest Corporation. The potential difference was measured at 14 random points and the average value was calculated. The average potential difference was converted into a connection resistance value, and electrical conductivity was evaluated based on the following criteria. The results are shown in Tables 4 and 5. A: Less than 3 ohms B: 3Ω or more, less than 6Ω C: 6Ω or more

[0180] [Table 4]

[0181] [Table 5] [Explanation of symbols]

[0182] 1...adhesive film for circuit connection, 2...first adhesive layer, 3...second adhesive layer, 4...conductive particles, 10...connection structure, 12...circuit electrode (first electrode), 13...first circuit member, 15...bump electrode (second electrode), 16...second circuit member, 17...circuit connection portion, 41...base particle, 41a...surface of base particle, 42...metal layer, 42a...outer surface of metal layer, 43...ceramic core material, 44...protrusion.

Claims

1. A film-like circuit connecting adhesive containing conductive particles, a first adhesive layer containing the conductive particles and a second adhesive layer provided on the first adhesive layer; the first adhesive layer contains a cured product of a photocurable component, The conductive particle has a base particle, a metal layer covering a surface of the base particle, and a ceramic core material disposed within the metal layer and protruding an outer surface of the metal layer; A circuit connecting adhesive, wherein d1 / l1 is 0.75 to 1.25, where d1 is the thickness of the metal layer and l1 is the length of the ceramic core in the thickness direction of the metal layer.

2. 2. The circuit connecting adhesive according to claim 1, wherein the metal layer has a thickness d1 of 110 to 190 nm.

3. 3. The adhesive for circuit connection according to claim 1, comprising a thermosetting compound, a latent curing agent, and a thermoplastic resin.

4. The adhesive for circuit connection according to claim 3 , wherein the thermosetting compound is at least one selected from the group consisting of oxetane compounds and alicyclic epoxy compounds.

5. The adhesive for circuit connection according to claim 3 or 4, wherein the thermoplastic resin is a phenoxy resin.

6. The adhesive for circuit connection according to any one of claims 1 to 5, wherein the first adhesive layer further contains a thermosetting component.

7. The adhesive for circuit connection according to any one of claims 1 to 6, which is used for connecting a plastic substrate with circuit electrodes to a semiconductor element.

8. The circuit connecting adhesive according to claim 7 , wherein the circuit electrode comprises titanium on a connecting surface.

9. A step of disposing the circuit connection adhesive according to any one of claims 1 to 8 between a first circuit member having a first electrode and a second circuit member having a second electrode; and a step of thermocompression bonding the first circuit member and the second circuit member to electrically connect the first electrode and the second electrode to each other via the conductive particles.

Citation Information

Patent Citations

  • Method of manufacturing connection structure, and connection structure

    JP2012227199A

  • Connection body, manufacturing method therefor, electronic component connection method and electronic component

    JP2016054288A

  • Conductive particles, conductive material, and connection structure

    WO2018181694A1